True food: an exploratory study of organic consumers in Cape Town - De Villiers, Simone (The IIE, 2016)
The purpose of this research study is to explore the mind-sets of individuals in Cape Town who consume organic food. Trust and credibility are key factors involved in consumers' purchase decisions, and in their relationship with brands. This research paper focuses on investigating how organic food brands can influence customer purchase decisions. The study investigates the behaviours, values, motivations and perceptions of organic food consumers in Cape Town, South Africa. In Cape Town, there are various organic food brands, such as retail brands and specialty brands, as well as farmers’ markets where consumers can purchase organic products. In depth research of the communications of specific organic food brands, and consumers, in Cape Town was done in order to gain an understanding of the current organic food market, as well as the consumers who are involved in this market. The data represents findings that reveal the communication strategies of organic food brands with regards to how they use these tools to build trust. In addition, the data represents the perceptions, knowledge and trust with organic consumers in Cape Town. The target population of the research study was females of all races between the ages of 18 and 35. Throughout the research, it was found that there was be a difference in transparency between retail brands, speciality brands and markets that sell organic products. In addition, there are different types of organic consumers, due to their organic food consumption habits and growing importance of health and environmental concerns. This study focused on two methods of data collection; an analysis of the brand communications of specific organic food brands in Cape Town as well as focus group interviews with organic food consumers. In addition to this, interviews with organic farmers in Cape Town were also conducted. The data analysis involved categorising the data into themes that were portrayed throughout the findings. The study involved Cape Town consumers' knowledge and behaviours towards organic food. It was found that there has been an emergence of considerations about the environment, ethical behaviour and health. The study revealed that organic food is no longer a niche market in Cape Town, but rather a rapidly growing 9 one. Thus, fresh and innovative ideas regarding the communications of organic food brands are needed to expand the industry and create more knowledge among consumers.
Thesis
Keywords: Cape Town; Organic food consumers; Organic food brands; Organic farmers; Organic food market